Agrivoltaics: an emerging technology for small-scale and urban agriculture - Thill, Alex J. (My University, 2025)
Agrivoltaics is the practice of producing crops or raising livestock under and around photovoltaic solar panels. With land increasingly in demand for both food and energy, agrivoltaic systems can help producers use land more efficiently. This report serves as a guide for farmers and educators exploring agrivoltaics for the use of urban or peri-urban agriculture. Solar power basics, system geometry, and types of arrays are discussed. Practical design including solar resource evaluation, determining spacing and panel configuration, power storage, and maintenance planning are critical for success. Using Kansas-based field experiments as case studies, we compare fixed-tilt, uniaxial tracking, and vertical-bifacial systems to evaluate how each configuration of panels affects crop light levels and site usability. Light characterization data under/around these arrays over a growing season are presented, and the importance of dead zones in agrivoltaics systems are discussed. In the report, worksheets and examples are provided to help guide growers through early design and consultation with licensed professionals. Our findings suggest that agrivoltaics must be site-specific, and are affected by the soil, climate, and farm management priorities at a given operation. Interdisciplinary collaboration and informed decision-making are encouraged to promote safe and efficient agrivoltaics systems that benefit small-scale, urban growers. For local and urban growers, agrivoltaics and co-located production as a farm operations strategy propose an opportunity to strengthen energy independence, improve land efficiency, and drive innovation in local, sustainable agriculture.
Keywords: Agrivoltaics; Co-located production; Solar energy; Land use; Photosynthetically-Available Radiation; Urban agriculture